A New Era for Crop Improvement： From Model- Guided Rationale Design to Practical Engineering - Chu, Chengcai (Molecular plant, 2015)
Photosynthesis is the basis of plant productivity. There is still a big gap between the efficiency of theoretical maximal photosyn- thetic energy conversion and the efficiency realized in the field. It was estimated that for C3 plants, the theoretical maximal energy conversion efficiency is ca. 4.6%, the observed maximal season- long energy conversion efficiency is about 2.4%, while the typical season-long energy conversion efficiency is only 0.8% （Zhu et al., 2010）. Despite this, however, photosynthesis has not been effectively used as a breeding target for crop improvement so far. When plants grow under elevated CO2, the crop yields are higher, clearly showing that enhancing photosynthesis can be used to improve yields （Long et al., 2006; Zhu et al., 2010）. Two reasons underlie the failure of improving photosynthesis for greater yields. First, photosynthesis is difficult to phenotype compared with other traits such as flowering time, plant height, leaf erectness, etc.; second, canopy photosynthesis, instead of leaf photosynthesis, is related to crop biomass and yield, however, there is no effective way to measure canopy photosynthesis and to identify the factors controlling canopy photosynthetic energy conversion efficiency.